2010
DOI: 10.2147/plmi.s14040
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fine needle aspiration biopsy as a diagnostic tool in pediatric head and neck lesions

Abstract: Background: Fine needle aspiration (FNA) biopsy is a well accepted diagnostic procedure and considered to be a valuable test for initial assessment of head and neck swellings in adults. The technique has gained popularity in the pediatric population over the last decade, with varying degrees of acceptance rates, accuracy, and results among pathologists. Objective: This study was performed to evaluate the utility of aspiration cytology as a first-line diagnostic tool in palpable head and neck masses in children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 13 publications
3
6
0
Order By: Relevance
“…The results of the present study were in concordance with Singh et al [13] who observed 71% cases of reactive LAD, 25.8% of granulomatous LAD, and 3.5% of acute suppurative LAD. Similar results with non-specific reactive LAD as predominant pattern were seen in studies by Handa et al [13] and Aggarwal et al [15]. On cytohistological correlation, there was one false-negative case were a case of Hodgkin's lymphoma was missed and reported as reactive LAD on cytology.…”
Section: Discussionsupporting
confidence: 86%
“…The results of the present study were in concordance with Singh et al [13] who observed 71% cases of reactive LAD, 25.8% of granulomatous LAD, and 3.5% of acute suppurative LAD. Similar results with non-specific reactive LAD as predominant pattern were seen in studies by Handa et al [13] and Aggarwal et al [15]. On cytohistological correlation, there was one false-negative case were a case of Hodgkin's lymphoma was missed and reported as reactive LAD on cytology.…”
Section: Discussionsupporting
confidence: 86%
“…Head and neck region is a common site for occurrence of many types of lesions and it poses a challenging diagnostic problem for the clinician. [ 2 ] The mass lesions in children can be of infective, reactive, cystic, developmental aberrations, or neoplastic in origin. [ 8 ] FNAC being a minimally invasive and cost-effective technique, it is being gaining acceptance in pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] It is now considered as the first diagnostic step in the evaluation of head and neck masses in pediatric population. [ 2 ] FNAC helps in triaging the mass lesions based on cytomorphological features, so that the patients can be treated or further investigations can be sought. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its introduction into the routine pediatric diagnostic algorithm has been fairly recent. [ 1 ] Although there are existing reports in the literature on utility of FNAC in the pediatric patients, the majority of such descriptions have included a specific body site or a particular disease entity. [ 2 - 4 ] Only occasional studies on pediatric FNAC have included both benign and malignant lesions encompassing various body sites.…”
Section: Introductionmentioning
confidence: 99%